Dynamic bidirectional relationship between financial inclusion and energy poverty: Evidence from China - Jiafeng Gu (Energy Reports, 2024)
Financial inclusion and energy poverty have an interactive relationship; however, this two-way relationship lacks sufficient research. This study investigates the two-way mechanisms of financial inclusion, energy poverty, and neighborhood spillover effects. Using a spatial simultaneous equation model, this study examines 2615 Chinese rural households in 2020. Results reveal a statistically significant positive interaction between financial inclusion and energy poverty. In addition, the neighborhood spillover effects of financial inclusion and energy poverty are both significantly positive, whereas their neighborhood interaction spillover effects are significantly negative.